GUEST COMPLAINT HANDLING USING THE LEAPS METHOD AT SELERA RESTAURANT NONGSA POINT MARINA & RESORT BATAM - Zainabul Hasna; Waryono (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This research is motivated by the importance of effective guest complaint handling in enhancing customer satisfaction and loyalty in the hospitality industry, particularly in Food & Beverage services. The research aims to describe guest complaint handling procedures using the LEAPS method (Listen, Empathize, Apologize, Provide Solution, Satisfy) at Selera Restaurant Nongsa Point Marina & Resort Batam. This research employs a qualitative phenomenological descriptive approach with data collection through participatory observation, in-depth interviews, and documentation study. Informants consisted of F&B Assistant Manager, F&B Supervisor, three waiters/waitresses, and three guests who had filed complaints. Data analysis utilized thematic analysis framework with hybrid deductive-inductive coding approach. Data validity was ensured through source and method triangulation, member checking, and prolonged engagement. Research findings indicate that LEAPS method implementation is conducted systematically through five sequential stages: Listen (active listening), Empathize (empathetic communication), Apologize (sincere apology), Provide Solution (providing alternative solutions), and Satisfy (satisfaction confirmation). The LEAPS method implementation proves effective in enhancing guest satisfaction and restoring trust in hotel services, with complaint resolution rate reaching 92% and guest satisfaction level at 88%.